PENDEKATAN GEOGRAFI HUKUM KRITIS DALAM KAJIAN HUKUM TATA RUANG INDONESIA: SEBUAH WACANA FILSAFAT HUKUM DAN INTERDISIPLIN - Nalle, Victor Imanuel W. (Penerbit Universitas Atma Jaya Yogyakarta, 2021)
The development of legal research shows the importance of an interdisciplinary approach in examining legal issues. Apart from that, legal issues also need to be examined more critically and not to see them as a product of a vacuum without the influence of non-legal factors. This paper explains the development of critical legal geography discourse as well as the theory of social space production and spatial justice associated with this discourse. The study of spatial law has developed an interdisciplinary approach with these critical theories with a critical legal geography framework. However, studies of spatial law in Indonesia have not developed much of this discourse in examining urban problems. Only a few researches on spatial law in Indonesia uses a critical legal geography perspective based on the tracing described in this paper. In fact, urban problems in Indonesia are similar to the phenomena that underlie the emergence of discourse on critical legal geography. Therefore, the study of spatial law in Indonesia requires a more philosophical and critical approach. Various new approaches developed in legal philosophy, one of which is critical legal studies, can be an analytical method for analyzing the influence of economy and power on spatial planning in Indonesia.